Fifteen-year experience of direct bridge with venoarterial extracorporeal membrane oxygenation to heart transplantationCentral MessagePerspective - Mojgan Laali, MD, PhD; Maharajah Ponnaiah, PhD; Guillaume Coutance, MD, PhD; Guillaume Hekimian, MD; Cosimo D'Alessandro, MD; Pierre Demondion, MD; Guillaume Lebreton, MD, PhD; Pascal Leprince, MD, PhD (JTCVS Open)
Objective: The study objective was to evaluate outcomes of patients directly bridged with venoarterial extracorporeal membrane oxygenation to heart transplantation. Methods: A single-center retrospective study was performed on 1152 adult patients undergoing isolated cardiac transplantation between January 2007 and December 2021. Among these, patients bridged with an extracorporeal membrane oxygenation to transplantation (extracorporeal membrane oxygenation group, n = 317) were compared with standard cohorts of patients (no extracorporeal membrane oxygenation group, n = 835). A period analysis (Era 1, 2007-2013, vs Era 2, 2014-2021) was performed. Results: Median duration of extracorporeal membrane oxygenation support before transplantation in the extracorporeal membrane oxygenation group was 8 days. Recipients of extracorporeal membrane oxygenation group were younger, with a better renal function and a shorter time on the waiting list. They were allocated to younger donors, with a longer ischemic time. The extracorporeal membrane oxygenation group and no extracorporeal membrane oxygenation group showed similar 1-year and 9-year survivals: 79.2% versus 79.4%, P = .98, and 56.2% versus 53.9%, P = .59, respectively. Period analysis in the extracorporeal membrane oxygenation group showed improved 1- and 9-year survivals in Era 2 compared with Era 1: 82.7% versus 71.1%, P = .021 and 60.4% versus 50.5%, P = .031, respectively. Era 2 was characterized by a higher rate of patients maintained on extracorporeal membrane oxygenation support after transplantation (92% vs 48%, P < .001), inserted mainly by peripheral cannulation (99.51% vs 57%, P < .001), for a shorter median duration after transplantation (5 vs 6 days, P = .033). Conclusions: Extracorporeal membrane oxygenation as a direct bridge to heart transplantation shows similar outcomes to standard cohorts of patients. In the extracorporeal membrane oxygenation group, the waiting list time is shorter due to the emergency allocation system, and recipients have no evidence of organ dysfunction at the time of transplantation.